A Novel Dominant-negative CARD11 Variant Causes Atopy and Immunodeficiency Syndrome - Kim My Le; Bayley E. Lindsay; Bradly M. Bauman; Kaisa Kettunen; Anne Ylinen; Meri Kaustio; Tapio Kesti; Nanni Mamia; Kaarina Heiskanen; Timi Martelius; Pasi Huttunen; Joshua D. Milner; et al. (Journal of Clinical Immunology, 2026)
Abstract CARD11 is a multidomain scaffolding protein essential for antigen receptor-induced NF-κB signaling in lymphocytes. CARD11 is highly intolerant to mutations, and pathogenic variants have been implicated in various immune-related disorders. In this study, we describe a family with a novel CARD11 missense variant, associated with immunodeficiency, cytopenia, and atopy. This study aims to characterize the phenotype associated with a novel CARD11 variant and to expand the current knowledge of CARD11’s role in lymphocyte function. Trio whole-exome sequencing identified a heterozygous CARD11 c.65 T > C variant that results in p.L22S substitution. The variant was shown to have a mild dominant-negative effect in an NF-κB reporter assay performed in transiently transfected CARD11 -deficient cells. Flow cytometry demonstrated decreased phosphorylation of p65 S529 and S6 S235/S236 in patients' T cells. In concordance with the dysregulated signaling, the patients present dampened activation and proliferation of T cells upon TCR-mediated stimuli. Moreover, transcriptomics analysis with differential expression and gene set enrichment analysis revealed dysregulation of genes involved in cell cycle regulation and inflammation. Our findings confirm that CARD11 is a central regulator of T cell signaling, and even mild loss-of-function can disrupt crucial pathways. Further studies are needed to gain a better understanding of the role of CARD11 in inborn errors of immunity and lymphocyte function.